Strategi Komunikasi Pemuka Adat Dalam Menjaga â€œTradisi Minjam Calon Pengantin Wanita Untuk Adaptasi Keluargaâ€ Di Desa. Ujanmas Baru, Kec. Ujanmas, Kab. Muara Enim - Ghea Frasilia Putri Utamia; Nuraid Nuraid; Manalullaili Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis discusses the Communication Strategy of Traditional Leaders in Maintaining "The Tradition of Borrowing Brides for Family Adaptation" in Ujanmas Baru Village, Kec. Ujanmas, Kab. Muara Enim, South Sumatra. The main problems in this study are how the communication strategy is carried out by traditional leaders in maintaining the tradition of borrowing from prospective brides in Ujanms Baru Village and what are the inhibiting factors faced by traditional leaders in maintaining the tradition of borrowing prospective brides in Ujanmas Baru Village. Based on these problems, the purpose of this research is to find out the communication strategy used by traditional leaders in maintaining the tradition of borrowing from the bride and groom in Ujanmas Baru Village and to find out the inhibiting factors faced by traditional leaders in maintaining the tradition of borrowing from prospective brides in Ujanmas Baru Village. The approach used in this study is a qualitative approach. The selected informants are those who have the relevance needed for research consisting of traditional leaders or traditional leaders, government, religious leaders, and the local community. data collection techniques using observation, interviews and documentation. Data were analyzed by descriptive qualitative supported by primary data and secondary data. The results of the study show that the strategy used by traditional leaders is to provide material to the younger generation regarding customs that exist in Ujanmas Baru Village with all local wisdom, traditional leaders use stories or fairy tales to teach customary values â€‹â€‹or norms in tradition to the community, especially the younger generation. When carrying out the tradition, traditional leaders usually invite the younger generation to be involved in it. Then in the tradition of borrowing the bride and groom, there are obstacles faced by traditional leaders, namely lack of support from stakeholders, ignorance of the community, especially the younger generation regarding customs, currents of globalization that are rife due to changing times which have reduced the interest of the younger generation and because of differences in traditions or customs in other regions.